ANALISIS KOMUNIKASI GREEN MARKETING INDOMARET TERKAIT KEBIJAKAN PLASTIK BERBAYAR - Akhmad Roqi Alawi; Daru Murti Raharjo; Alifiansyah Deto Rahmana Putra (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze green marketing communication in the implementation of the paid plastic bag policy at Indomaret. It employs green marketing concepts and framing theory to examine how environmental messages are constructed and delivered to consumers. A qualitative content analysis method was applied to visual communication, product-based communication, and verbal communication at the point of sale. Data were collected from pamphlets, alternative products, and cashier–consumer interactions. The findings reveal that green marketing communication is fragmented rather than integrated. Visual communication symbolically frames environmental issues, product communication combines sustainability values with marketing strategies, while verbal communication is dominated by regulatory and economic framing. This fragmentation creates a gap between symbolic representation and operational practice, resulting in a partial understanding of environmental messages among consumers. These findings highlight the importance of consistency across communication channels to ensure a more comprehensive understanding of sustainability messages. Keywords: Green marketing, Communication framing, Environmental communication, Fragmented communication, paid plastic bag policy